2014
DOI: 10.1007/s10832-014-9974-5
|View full text |Cite
|
Sign up to set email alerts
|

Study on improving current generating time of piezoelectric energy harvesting system

Abstract: This study combined a ceramic, metal alloy, and polymer in a piezoelectric energy harvesting system. The proper container film for curing the urethane rubber was determined to be a Si-coated polyester film. Furthermore, a technique was developed to embed a piezoelectric energy system in urethane rubber (soft and hard); the resulting effects on the output voltage generation of this system were experimentally determined. Comparing the uncoated and hard urethane rubber-coated systems, the latter system improved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A first prototype of the TMPD was designed and fabricated as shown in Figure 3 so as to generate electricity by hitting the piezocomposite element through the motion of the mass since a former study on the piezocomposite element itself [6] reported that the best efficiency was obtained by hitting the element.…”
Section: A Test Using Shaking Table In Horizontal Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…A first prototype of the TMPD was designed and fabricated as shown in Figure 3 so as to generate electricity by hitting the piezocomposite element through the motion of the mass since a former study on the piezocomposite element itself [6] reported that the best efficiency was obtained by hitting the element.…”
Section: A Test Using Shaking Table In Horizontal Directionmentioning
confidence: 99%
“…Therefore, the piezoceramic is generally combined with other materials to form a piezocomposite [4,5]. In the present application, the piezoceramic is combined with and stainless steel plate so as to improve the resistance to shocks and the electricity generating efficiency of the piezoelectric [6].…”
Section: Introductionmentioning
confidence: 99%